ANALISIS HUBUNGAN KARAKTERISTIK INDIVIDU, SAFETY LEADERSHIP, MOTIVASI, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN CV. ETERNA GARMENT - Dhia Ghoniyyah; Yuliani Setyaningsih; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Globalization makes business competition become increasingly tight, so it takes the company's efforts to compete by improving and maintaining the quality of employee performance. Performance is the result of concrete, observable, and measurable work. Employee performance means an ability to achieve job requirements. In performance there are three factors that can affect one’s performance, those factors are individual factors, psychological factors, and organizational factors. CV. Eterna Garment is a company in the garment industry, this company continues to develop so that the required performance improvement to employees so the quality issued for the market can be guaranteed good. The research aimed to analyze the relationship of individual characteristics, safety leadership, motivation, reward and punishment on employee performance. The type of research used is analytical with cross sectional method. The sample used in this research is 50 employees with total sampling. The data was collected by questionnaire by respondent. Based on the result of research using Chi-Square test showed that the related variables were safety leadership (p = 0,003), motivation (p = 0,028), reward and punishment (p = 0,022). While unrelated variables are age, sex, years of service and education.